IMF Committee on Balance of Payments Statistics : Annual Report 2000. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2001)
The IMF Committee on Balance of Payments Statistics was established in 1992 to promote accuracy and cooperation in the compilation of balance of payments statistics. Membership of the Committee, which advises the IMF on statistical issues, consists of representatives from a number of international organizations, central banks, and national statistical offices. The Committee's annual report for 1999 discusses recent trends in global balance of payment statistics and highlights the Committee's work program.